In-reach clinical pharmacology and toxicology service at a tertiary care hospital: preliminary audit findings - Dhiraj Ravindran Selvaraj; Laurence Alexander Gray; James Michael Coulson (Clinical Medicine)
Introduction: Adverse drug reactions and poisonings contribute to 16.5% of hospital admissions. We established an in-patient medical toxicologist service given that evidence suggests this reduces length of hospital stay and improves patient outcomes.1–3 Methods: We prospectively collected data from in-patients in the emergency department (ED), Clinical decision unit (CDU) and medical assessment unit (MAU) in a tertiary care hospital. Patients were identified for inclusion at the morning handover and screening of in-patient electronic lists. The service started in October 2024 and constituted twice-weekly rounds. Data were collected on MS Forms through secure servers and analysed using SPSS v. 22.0. Results: In our audit, we included 43 patients reviewed over 24 service days. Median (IQR) age was 36 (26–52) and 26 patients ((60.5%), p=0.17) were women. Thirty (69.8%) presented via ambulance. Thirty-nine presentations (90.3%) were related to overdose, while other presentations included hypertensive emergencies and adverse drug reactions. Thirty-two (74.4%) cases were initially managed by emergency physicians and specialist reviews following a verbal handover among 37 (86.1%) patients. Twenty-two (51.2%) cases were seen in the CDU. The median time to specialist review from admission with the twice-weekly service was 14 h 23 min (IQR 8 h 39 min–33 h 11min). All the cases referred were appropriate for clinical pharmacologist/ toxicologist review and 12 (27.9%) were discharged from hospital following review. The median (IQR) duration of stay was 1 day (0–3 days) and 1 (2.3%) patient died from sepsis secondary to discitis. Conclusion: Our audit demonstrated that a clinical pharmacology and toxicology in-reach service is feasible, with most referrals related to the management of overdoses. Integrating specialist services with ED and utilisation of CDU facilitate early reviews and discharge, improving hospital flow and patient experience. In the future, a routine service beyond 2 days could include more patients and facilitate quicker turnaround times